Research on intelligent level of the brain of computility network - WANG Chen; ZHAO Peng; TANG Guohua; WANG Xiaohan; YUAN Xiangyang (Dianxin kexue)
Brain of computility network is the intelligent center of computility network, and it is the key system to realize multi-element orchestration and scheduling of computility network. Intelligence is the core of realizing and improving the flexible, agile and efficient orchestration, management and operation capability of the brain of computility network. Many companies in the communication industry have focused on the introduction of intelligent technology of the brain of computility network on the basis of the early realization of the products, and put forward high expectations for the intelligent evolution of the brain of computility network in the future. However, at present, there is no systematic evaluation method for the intelligence level of the brain of computility network, which cannot well evaluate the intelligence level, upgrading stages and key indicators to be optimized. Based on the existing work and demand analysis in the industry, the goal and stage capability of the intelligent evolution of the brain of computility network were studied, and a classification method of the intelligent level of the brain of computility network was put forward, which included detailed steps such as the selection of the evaluation object, the decomposition of the evaluation process, the consideration of the constraint indicators, and a complete set of rules for the evaluation of the intelligent level of the brain of computility network. Finally a concrete application example was given. The proposed method can effectively quantify the specific level of the brain of computility network system, clarify the direction and index of its evolution to the next level, and provide reference for industry intelligent evaluation and system construction.